Cost reduction associated with transradial access in percutaneous coronary intervention: A report from a Japanese nationwide registry - Satoshi Shoji; Shun Kohsaka; Hiraku Kumamaru; Kyohei Yamaji; Shiori Nishimura; Hideki Ishii; Tetsuya Amano; Kiyohide Fushimi; Hiroaki Miyata; Yuji Ikari (Elsevier, 2022)
Summary: Background: Percutaneous coronary intervention (PCI) is increasingly performed via transradial access (TRA). This study aimed to investigate the clinical and economic benefits of TRA compared with transfemoral access (TFA) under universal healthcare coverage system in Japan. Methods: A total of 36,153 patients (acute coronary syndrome [ACS], 15,266; stable ischemic heart disease [SIHD], 20,052) across 714 institutions in the Japanese nationwide PCI registry (J-PCI) in 2015 were analyzed (mean age 69.9 ± 11.1 years and 23.6% female). Cost was defined as the total amount of healthcare resources used to care for the patient during hospitalization. Propensity score matching analysis was conducted to balance the baseline characteristics of patients undergoing TRA and TFA. Findings: The median total cost of PCI was JPY 1,341,176 (interquartile range, 959,052), with higher expenses for ACS (JPY 1,772,116 [1,117,107]) compared with SIHD (JPY 1,119,153 [540,440]) patients. Most patients underwent PCI via TRA (73.8%), and after propensity score matching, TRA was associated with a reduced risk of in-hospital death and bleeding (0.88% vs. 1.91% [P < 0.0001] and 2.18% vs. 4.53% [P < 0.0001] in ACS, and 0.10% vs. 0.28% [P = 0.070] and 0.53% vs. 1.72% [P < 0.0001] in SIHD, respectively), which led to lower costs in both ACS (JPY 1,699,279 [1,164,554] for TRA vs. JPY 1,931,255 [1,070,222] for TFA; P < 0.0001), and SIHD (JPY 1,102,352 [505,904] for TRA vs. JPY 1,311,525 [706,450] for TFA; P < 0.0001) patients. Interpretation: In this direct cost analysis of a nationwide registry, the use of TRA was associated with cost saving for both ACS and SIHD patients. Funding: This study was funded by the Japan Society for the Promotion of Science (grant nos. 20H03915, 16H05215, 16KK0186, 20K22883, and 21K08064), Japan Agency for Medical Research and Development [AMED] (grant number 16lk1010004h0002), and the National Clinical Database. The J-PCI registry is led and supported by the Japanese Association of Cardiovascular Intervention and Therapeutics.